Role of Indigenous Arqiyat Distillery in conservation of Rosa species - Shujaul Mulk Khan,; Habib Ahmad, (International Journal of Phytomedicine, 2014)
Cultivation of Rosa damascene in Pakistan is not a common practice. It was a common shrub of salt range and adjacent subtropical zone of Pakistan. Due to over grazing, agricultural expansion, increase in population and habitat loss a lot of its population has lost in the region [4, 5, 6]. Nevertheless, it’s quite abundantly grown in the outskirts of Kallar Kahar Lake where there few distilleries exist since last 300 years. Arqiyat are produced in these distilleries, of which Arqe Gulab is the famous one (Fig. 1 & Fig. 2). Main objective of this short communication is to revealed on traditional and scientific communities that traditional medicinal knowledge and use of such distilleries play a vital role in the conservation of many species including Rosa damascene.